Representasi Tingkat Kepuasan Pemustaka Terhadap Efektivitas Pemanfaatan Sistem Informasi Perpustakaan Digital pada Perpustakaan Perguruan Tinggi Islam di Yogyakarta - Mukhlis Mukhlis (Program Studi Ilmu Perpustakaan UIN Alauddin, 2015)
Academic library, as an information media to support learning process, is supposed to provide collections that users need. The current study is a descriptive research with using qualitative approach. As the research instrument, an interview guide was made in order to get neccassary data. The focus of study is user satisfaction on digital library information systems at the UIN Sunan Kalijga library, Yogyakarta. The research findings shows that user expectation or the succeed users in using its digital system was higher than failure level in usage. Therefore, the digital library information systems has been working properly.